Efficacy of Sound Touch Elastography in Assessing Subcutaneous Lipohypertrophy from Insulin Injections - Xu J; Cheng F; Dai Y; Yu S; Chen W; Zhou R (Diabetes, Metabolic Syndrome and Obesity)
Ji Xu,1 Fuming Cheng,2 Ying Dai,2 Shuting Yu,2 Wanjun Chen,1 Ruhai Zhou1 1Department of Ultrasound Medicine, Affiliated People’s Hospital of Ningbo University, Ningbo, Zhejiang, 315040, People’s Republic of China; 2Department of Endocrinology and Metabolic Diseases, Affiliated People’s Hospital of Ningbo University, Ningbo, Zhejiang, 315040, People’s Republic of ChinaCorrespondence: Ying Dai; Ji Xu, Affiliated People’s Hospital of Ningbo University, No. 251, Baizhang East Road, Yinzhou District, Ningbo, Zhejiang, 315040, People’s Republic of China, Email hopemmz@163.com; lucky15158039789@163.comObjective: Lipohypertrophy (LH) is a localized complication of type 2 diabetes mellitus in patients on long-term insulin therapy. Sound touch elastography (STE) is a crucial tool in the quantitative real-time assessment of tissue hardness within specific target regions. This study aims to explore the efficacy of STE in evaluating the hardness of subcutaneous LH at insulin injection sites in individuals with type 2 diabetes mellitus and investigate the correlations between the hardness of LH lesions and various clinical indicators.Methods: A cohort of 53 individuals with type 2 diabetes mellitus undergoing insulin therapy at the Department of Endocrinology, Affiliated People’s Hospital of Ningbo University from April 2023 to January 2024 was selected. General clinical data of the participants and STE-derived Young’s modulus hardness values of the LH lesions and adjacent normal adipose tissue were collected. The Wilcoxon signed-rank test was employed for comparative analysis between the two tissue groups, while Spearman’s rank correlation was used to examine the relationships between Young’s modulus values of the LH lesions and clinical indicators.Results: Routine ultrasound examination revealed LH in all 53 participants. The maximum (Emax), average (Emean), and minimum (Emin) values of Young’s modulus significantly differed between the LH lesions and surrounding healthy adipose tissue (Z=− 6.334, P< 0.001; Z=− 6.263, P< 0.001; Z=− 5.865, P< 0.001, respectively), indicating greater hardness in the LH lesions. Additionally, the Emin values of the LH lesions were positively correlated with the glycated hemoglobin levels (r=0.293, P< 0.05).Conclusion: Ultrasound elastography-based STE exhibits great potential in assessing LH hardness in individuals undergoing insulin therapy for type 2 diabetes mellitus. STE offers a novel and objective ultrasonographic approach for accurately evaluating LH severity, highlighting the significance of this technique in clinical diagnostics.Keywords: ultrasound elastography, type 2 diabetes, lipohypertrophy, insulin injections